2018
DOI: 10.1016/s2213-2600(18)30326-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal carbon dioxide removal for lowering the risk of mechanical ventilation: research questions and clinical potential for the future

Abstract:  Extracorporeal carbon dioxide removal is an emerging therapy for the treatment of acute respiratory failure.  There is limited evidence to support the routine use of ECCO 2 R, outside of clinical trials, in patients with acute respiratory failure.  Future research should focus on veno-venous ECCO 2 R.  Further research is required to optimise the technology and identify if modifications can be made, especially to permit the use of less anticoagulation than is currently needed.  ECCO 2 R may have a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 72 publications
5
55
0
2
Order By: Relevance
“…It should be noted that although extracorporeal CO 2 removal for lung-protective ventilation is feasible, it is neither evidence-based nor is it universally available. 39 Occasionally, patients develop concomitant or discrete cardiac failure-mainly from myocarditis, myocardial infarction, or sepsis-related cardiomyopathy-and might need venoarterial ECMO. Provision of ECMO in the setting of both pulmonary and cardiac dysfunction is particularly complex and, where possible, requires close liaison with an expert extracorporeal life support centre before ECMO initiation.…”
Section: Quality Assurance and Collaborative Researchmentioning
confidence: 99%
“…It should be noted that although extracorporeal CO 2 removal for lung-protective ventilation is feasible, it is neither evidence-based nor is it universally available. 39 Occasionally, patients develop concomitant or discrete cardiac failure-mainly from myocarditis, myocardial infarction, or sepsis-related cardiomyopathy-and might need venoarterial ECMO. Provision of ECMO in the setting of both pulmonary and cardiac dysfunction is particularly complex and, where possible, requires close liaison with an expert extracorporeal life support centre before ECMO initiation.…”
Section: Quality Assurance and Collaborative Researchmentioning
confidence: 99%
“…Some studies showed that an early use of V-V ECMO in respiratory distress may minimize respiratory-driven pressure and reduce pulmonary and systemic inflammation as well as severe multiorgan dysfunction [11,12]. Therefore, V-V ECMO is a feasible option in COVID patients not responding to conventional interventions resulting in improved outcome and lung protection [13].…”
Section: Covid-related Severe Respiratory Impairment and V-v Ecmomentioning
confidence: 99%
“…First, the current model only predicts the relationship between acid‐base chemistry and the ECCO 2 R rate; thus, the current approach is general and not dependent on the performance characteristics of a specific device. In practical clinical applications, the predictions from the current model may require supplementary data relating the ECCO 2 R rate to the blood flow rate for a specific device . Second, the current model is limited by the assumption of steady state conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There are several ECCO 2 R devices currently available with varying abilities to remove CO 2 depending on the rate of blood flow through the device and the surface area available for transmembrane diffusion. These devices have generally been categorized as lower or higher CO 2 extraction devices with the former containing relatively small membrane surface area using blood flow rates ≤500 mL/min and the latter containing relatively large membrane surface area using blood flow rates >500 mL/min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation